Menakar Urgensi Pendidikan Multikulturalis Masuk Kurikulum - Tumpal Daniel (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2019)
Being aware of religious life and nation is inseparable, while the reality of Indonesian nation is very diverse in terms of tribe, religion, race and among groups (SARA). This condition is certainly potentially disrupt harmonization and harmony that led to conflict. Indonesian Muslims become the determinant factor of harmonization and religious harmony in Indonesia. This is because the majority of Muslims from the side of theology theologically bring the universal message of peace "rahmatan lil alamin". In the context of Indonesia-an has been proven that the entry and spread of Islam in the archipelago filled with stories of harmonization and harmony both with the culture of indigenous communities and with religions that first present in the archipelago.Talking about the harmony of religious people, like ideals and facts that are not in line. The question is why is it so difficult to create harmony ?. It can be seen as an indication that the community actually has not gained a proportional understanding of the concept of a harmonious religious life ". This cultivation of understanding can not be instant only through socialization and orientation, but must be through regular and well-planned education.One solution offered from this research is to include the Education of Culturalis into the school curriculum.